How to practice the return and +1s in women`s professional tennis - Born, P.; Vogt, T. (Coaching and Sport Science Review, 2022)
The aim of this article is to present stroke placements of the return, the 3rd stroke and 4th stroke in professional women`s tennis. Based on recent scientific insights (Born et al., 2021), training recommendations as well as practice patterns will be derived from these results. For returns, training recommendations include aiming to the middle zones and longer than the service line. For 3rd strokes, it is recommended to e.g., train hitting into the c-zones, whereas for 4th strokes this is e.g., hitting more frequently to the backhand or, respectively, the weaker side of the opponent. Practice patterns are exemplified for each stroke.